1979
DOI: 10.1177/101269027901400202
|View full text |Cite
|
Sign up to set email alerts
|

Why Man Climbs Mountains

Abstract: This paper is a report on the results of a study of 266 members of the Alpine Club of Canada, Calgary Section. The study attempted to gain further insight into why people climb mountains. The results indicate that an everchanging mosaic of primary and secondary motives for climbing exist. Age, ability and sex would appear to be three of the stronger determining variables that influence this mosaic. A model for characterizing motives for participation in physical activity is suggested. The categories of the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…This appears to be the first formal recognition, description and analysis of rush. Sensations which seem to correspond to rush, as defined here, have been mentioned by participants in some previous studies, but as "inef-fable" or "indescribable" (Allman, Mittelstaedt, Martin, & Goldenberg, 2009;Bratton, Kinnear, & Korolux, 1979).…”
Section: Risk Recreation Paradoxsupporting
confidence: 58%
See 1 more Smart Citation
“…This appears to be the first formal recognition, description and analysis of rush. Sensations which seem to correspond to rush, as defined here, have been mentioned by participants in some previous studies, but as "inef-fable" or "indescribable" (Allman, Mittelstaedt, Martin, & Goldenberg, 2009;Bratton, Kinnear, & Korolux, 1979).…”
Section: Risk Recreation Paradoxsupporting
confidence: 58%
“…Age, gender, activity, difficulty, prior skill, definitions and analytic methods differ between studies, with no overall patterns apparent. Climbing and mountaineering have been studied most frequently, with at least 15 analyses in the past three decades (Berger & Greenspan, 2008;Bratton et al, 1979;Breivik, 1996;Carnicelli-Filho, Schwartz, & Tahra, 2010;Delle Fave, Bassi, & Massimini, 2003;Ewert, 1985Ewert, , 1993Ewert, , 1994Feher, Meyers, & Skelly, 1998;Kiewa, 2001;McIntyre, 1992;Mitchell, 1983;Pomfret, 2011;Rossi & Cereatti, 1993). There are ≥11 analyses of whitewater rafting and kayaking (Arnould & Price, 1993;Arnould et al, 1999;Carnicelli-Filho et al, 2010;Cater, 2006;Cater & Cloke, 2007;Fluker & Turner, 2000;Holyfield, 1999;Holyfield & Fine, 1997;Jones, Hollenhorst, Perna, & Selin, 2000;McGillivray & Frew, 2007;Wu & Liang, 2011); 2≥7 of skydiving and parachuting (Allman et al, 2009;Carnicelli-Filho et al, 2010;Celsi, Rose, & Leigh, 1993;Klausner, 1967;Lau-rendeau, 2006;Lipscombe, 1999;Lyng & Snow, 1986); ≥6 of surfing and sailboarding (Buckley, 2002a(Buckley, , 2002bDolnicar & Fluker, 2003;Farmer, 1992;Irwin, 1973;…”
Section: Adventure Motivationsmentioning
confidence: 99%
“…A large strand of this research has concentrated on the reasons why people pursue extreme and/or risky sports, because to the outsider it is not inherently obvious. There has been a great deal of motivational research on endurance endeavours such as marathon running and mountain climbing, (Bratton, Kinnear & Koroluk, 1979;Bull, 1988;Burnick & Topic, 2003;Leedy, 2000;Males, Kerr & Gerkovichl, 1998;Ogles & Masters, 2003;Weinberg, 1998). Ogles & Masters (2003) sought to understand what motivates people to undertake marathons when they require a large quantity of arduous training which is well beyond the level needed to maintain health and wellbeing.…”
mentioning
confidence: 99%
“…This work has shown that social involvement is not very important as a reason for participation. In addition, some unique sports participants (hang-gliders, skydivers, mountain climbers) also have not highly valued social Involvement as a motive for participation (Brannigan & McDougall, 1983;Bratton et al, 1979;Duthie & Salter, 1981). The unique sports of hang-gl1dtng, ~ skydtvlng, and mountain climbing, however, are perhaps ultimately more…”
Section: Discussion Of Motives For Participation Resultsmentioning
confidence: 99%
“…In a broader based study, Bratton, Kinnear, and Koroluk (1979) 4 attempted to gam insight into motlVes for mountam climbmg. The responses of 266 members of a mountain climbing club were studied The mean age was 37 and 80% of the climbers were male.…”
Section: Current Research Perspectivesmentioning
confidence: 99%